Hydroa vacciniforme-like lymphoproliferative disorder in a 13-year-old boy. - Porras-Sanchez, N.R.; Villamil, J.; Gutiérrez, A.M.; Pastrana-Tovar, V.; Quevedo, E.; Rolón Cadena, M.; Motta Beltrán, A. (European Journal of Pediatric Dermatology, 2022)
Hydroa vacciniforme is an uncommon chronic photodermatosis that causes scarring and may be related to Epstein-Barr virus infection and higher risk of developing cutaneous lymphomas. We present the case of a 13-year-old boy suffering from chronic deforming ulcers of the face and ears. The serological investigations showed a previous exposure to the Epstein-Barr virus. The histopathological study revealed a marked lymphocyte infiltrate with angiocentrism, suggesting the diagnosis of hydroa vacciniforme. Immunohistochemistry confirmed the diagnostic suspicion, showing positive markers of Epstein Barr virus associated cutaneous lymphoma.